FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yumita Rahmawati; Bambang sudiyatno (Dinamika Akuntansi Keuangan dan Perbankan, 2018)
This study aims to analyze the effect of profitability, growth, liquidity, debt to equity ratio (DER) to dividend policy. About 128 samples used from annual report of mining companies listed on the Indonesia Stock Exchange in the period of 2013 -2016. The analytical method is using the logistic regression analysis method. The result of thids study is only profitability that affects to dividend policy (coefficient logistic regression: 0.220). It means if profitabillity is risen, the other variabels are constan. Therefore, dividends will be distributed if the company makes a profit. The company's ability to get greater profits will increase dividends distributed to shareholders. Key Word: profitability, growth, liquidity, debt to equity ratio (DER), dividend policy